(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
This paper presents a preliminary analysis of the marble head of the goddess Hygieia from the excavation in the “Terme Milano” at Gortys. Through the morphological and stylistic study of the artifact, it aims to analyze the historical context and recognize the specific sculptural production. The examination of the somatic details and of the accurate hairstyle allows to recognize the sculpture as one of the representation of the goddess Hygieia, belonging to the “Hope” type. The head is also related to other representations of the goddess founded in Gortys.